Effect of Degree of Polarization on Localized Spin Density in Tightly Focusing of Vortex Beams - Zixuan Wang; Chencheng Yan; Zhen Dong; Fei Wang; Yahong Chen; Yangjian Cai (IEEE Photonics Journal, 2022)
The transverse spin and orbital-to-spin angular momentum conversion during strong focusing of light beams have attracted wide interest due to the novel physics behind and their broad potential applications. In this work, we study the effect of incident beam’s degree of polarization on the localized spin density of a tightly focused field. By modulating the correlation strength between two orthogonally polarized vortex modes of the incident beam, we find that the magnitude of the focal-plane transverse spin density component changes only slightly, while its spatial shape becomes an isotropic spin vortex with the decrease of the incident degree of polarization. Whereas, the longitudinal spin density, induced by the vortex phase, reduces its magnitude significantly with the decrease of incident beam’s degree of polarization. The behavior of the focal-plane spin density is interpreted with the two-dimensional degrees of polarization among the tightly focused field components. Furthermore, we explore the roles of the topological charge on enhancing the longitudinal spin density for unpolarized incident beam. Our results reveal the feasibility of spin-orbit interaction with partially polarized or even completely unpolarized light, such as the thermal light.